East African pigs have a complex Indian, Far Eastern and Western ancestry. (22nd May 2015) - Noce, A.; Amills, M.; Manunza, A.; Muwanika, V.; Muhangi, D.; Aliro, T.; Mayega, J.; Ademun, R.; Sànchez, A.; Egbhalsaied, S.; Mercadé, A.; Masembe, C.
Summary In this study, we have characterized the mitochondrial diversity of 81 swine from Uganda. Median‐joining network analysis of D‐loop sequences from these individuals and others characterized in previous studies allowed us to determine that Ugandan pigs cluster with populations from the West (Europe/North Africa), Far East and India. In addition, partial sequencing of the Y‐chromosome UTY locus in 18 Ugandan domestic pigs revealed the segregation of a single HY1 lineage that has a cosmopolitan distribution. A Western and Far Eastern ancestry for East African pigs had been already reported, but this is the first study demonstrating an additional contribution from the Indian porcine gene pool. This result is consistent with the high frequency of zebuine alleles in cattle from East Africa. The geographic coordinates of East Africa, at the crossroads of many trading routes that, through the ages, linked Europe, Africa and Asia, might explain the rich and complex genetic heritage of livestock native to this area.